Pengaruh Disiplin Kerja terhadap Kinerja Karyawan Rumah Sakit dalam Masa Pandemi Covid 19 - Kelana Sri Hafidah; Farida Gustini (Jurnal Health Sains, 2021)
The Covid 19 pandemic has many impacts including in the health care environment and medical personnel. Lack of PPE, lack of good patient screening in health facilities, fatigue of medical personnel due to the growing number of COVID-19 patients and long working hours, as well as psychological distress. The purpose of this research was to determine the effect of work discipline on employee performance in X Hospital in pandemic covid 19. The kind of this research method was quantitative of cross-sectional study. The population of this study were all employees at X Hospital as many as 98 employees with a total population of 98. Data obtained from the respondent used questionnaire, then data analysis of this research used Kendall Tau test.The result showed that some respondents in X Hospital had enough worked discipline with sufficient performance. The correlation of Kendall Tau test showed that p=0.001 < α= 0.05 with the correlation 0.290 means that the correlation was weak category.The conclusion of this research that there was an effect of work discipline on employee performance in X Hospital. The advice given by researcher for X Hospital was to increase the responsibility to employees that employee’s practice that sustains of work discipline and improved the sanctions for employees who not arrive on time when the working begins.